Properties Enhancement of Rubber Wood Particleboard Laminated with Low Density Polyethylene (LDPE) Resin - Fauzi Febrianto; See P Hwee; Ching K Man; Wahyu Hidayat (Jurnal Ilmu dan Teknologi Kayu Tropis, 2012)
The main weaknesses of particleboard are that it has a lower strength and a lower dimensional stability compared to solid wood. Therefore, in order to gain excellent properties prior to be used, it needs some treatments, i.e., resin thermoplastic laminated. The objectives of this study were to improve the physical and mechanical properties of rubber wood particleboard laminated with low density ethylene (LDPE) resin. Rubber wood particleboard was laminated with 4 different concentrations of LDPE resins (i.e., 5, 10, 15, and 20%). The physical and mechanical properties of board were evaluated both in dry and wet states. The results indicated that the dimensional stability of board after laminated with LDPE resin showed significant improvement in term of water absorption and thickness swelling. Modulus of rupture and srew resistant of resulted particle board were increased with addition of LDPE resin. Modulus of elasticity and surface hardness of the particleboard were slightly decreased with addition of LDPE resin. The intenal bond was unchanged. The best treatment was found on lamination the surface of particleboard with 5% LDPE resin. All the physical and mechanical properties of particleboard laminated with 5% LDPE resin met the requirements of JIS A 5908-2003 standard.Key words: dimensional stabilization, low density polyethylene, mechanical properties, particleboard